Taxonomy and Identification of Principal Foliar Nematode Species (Aphelenchoides and Litylenchus) - Zafar Handoo; Mihail Kantor; Lynn Carta (Plants, 2020)
Nematodes are Earth’s most numerous multicellular animals and include species that feed on bacteria, fungi, plants, insects, and animals. Foliar nematodes are mostly pathogens of ornamental crops in greenhouses, nurseries, forest trees, and field crops. Nematode identification has traditionally relied on morphological and anatomical characters using light microscopy and, in some cases, scanning electron microscopy (SEM). This review focuses on morphometrical and brief molecular details and key characteristics of some of the most widely distributed and economically important foliar nematodes that can aid in their identification. Aphelenchoides genus includes some of the most widely distributed nematodes that can cause crop damages and losses to agricultural, horticultural, and forestry crops. Morphological details of the most common species of Aphelenchoides (A. besseyi, A. bicaudatus, A. fragariae, A. ritzemabosi) are given with brief molecular details, including distribution, identification, conclusion, and future directions, as well as an updated list of the nominal species with its synonyms. Litylenchus is a relatively new genus described in 2011 and includes two species and one subspecies. Species included in the Litylenchus are important emerging foliar pathogens parasitizing trees and bushes, especially beech trees in the United States of America. Brief morphological details of all Litylenchus species are provided.